A critical examination of the provisions of the legislation dealing with marine living resources from an enforcement and prosecutorial perspective and recommendations to ensure more effective enforcement and prosecution - Snijman, Philippus Johannes (Institute of Marine and Environmental Law, 2026)
Effective enforcement of legislation firstly and foremost depends on the quality of such legislation. The purpose of this dissertation is not only to critically examine the legislation dealing with marine living resources from the viewpoint of criminal enforcement, but also to contribute to effective enforcement by proposing possible solutions. Recent history has shown both what the almost disastrous effects of poorly drafted legislation can be, but also how relatively simple amendments can make a huge difference in drastically improving the success of enforcement and prosecution2. Convictions in abalone related offences shot up from an extremely low, but unfortunately unknown, figure to as high as eighty five per cent after the amendments of 20033 to the regulations regarding abalone.4 The success can also be partly attributed to a more efficient system for the handling and identification of seized abalone, as well as a dedicated court to hear such matters, but the role of the amendments to the legislation was crucial to the outcome.